ENGLISH TEACHER'S PERSPECTIVE : ONLINE LITERATURE CIRCLES STRATEGY TO ENHANCE YOUNG LEARNER'S VOCABULARY ENGAGEMENT - Afifah Mufidati; Oikurema Purwati (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
AbstractThe purpose of the present study was to investigate teachers perceptions of their experiences with online literature circles across young learner at age 8-12 years old. Data gained from five English teachers from different schools and having experience minimum 3 months in teaching English. Data analysis was conducted primarily using qualitative descriptive. The discussion found that online literature circles has been used by some teachers although the implementation did not run as the principle. In addition online literature circles has potential enhance students vocabulary engagement due to group discussion activities and teachers observation. However, young learner should emphasize more chances to make them more familiar with discussion and reading material.